PENGARUH PEMBIAYAAN BERMASALAH DAN RASIO LIKUIDITAS TERHADAP TINGKAT PENGEMBALIAN MODAL PADA PT BANK SYARIAH MANDIRI - Rizki Zulfikar; Raden Rivan Primawan (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
This study aims to analyze the the influence of Non performing finance And Financing to deposit ratio on Return on equity. Phenomenon occuring in PT Bank Syariah Mandiri in some periods there was an increase Non performing finance but followed by rise Return on equity and increase Financing to deposit ratio but followed by a decline in Return on equity Methode used in this research is descriptive verification method. The sample used in this study is one company and the last 8 years of financial statement data in quartal (time series) so the amount in this study were 32 of data (pooled data) and the analytical tool used is the classical assumption test, multiple regresion, correlation analysis, the coeffecien of determination with hypothesis testing using Test-T and Test-F with the help of SPSS 16.0 for windows. The partial result of research showed the Non performing finance effect negative significant toward Return on equity of 65,56% and Financing to deposit ratio effect not significant toward Return on equity of 1,85%. While jointly simultaneously, Non performing finance And Financing to deposit ratio have an influence on Return on equity of 66,4% and the remaining 33,4% is influenced by other factor. Keywords : Non performing finance, Financing to deposit ratio, and Return on equity.